Comparison of terrain corrections based on the point source and line source DC methods - Xie, Haijun; Li, Lu; Li, Zhiqiang; Li, Jingrui; Li, Gang; Li, Wanlu (Frontiers in Earth Science, 2022)
In the DC method of exploration, the topographic relief causes the apparent resistivity curve to be distorted. In order to eliminate the influence of terrain fluctuations, the paper selects two undulating terrains of valley and ridge, uses unstructured triangular mesh to solve the region, selects the wave number k and coefficient g obtained by integral equation method, and uses COMSOL MULTIPHYSICS to perform point power and line respectively. The power supply finite element two-dimensional model forward modeling, and the terrain correction is performed by the comparison method and the conformal transformation method respectively. The results show that the theoretical curve of the line power supply and the theoretical curve of the point power supply are very similar, but the quantitative characteristics of the two curves are not exactly the same; the comparison method is applicable to the line power supply and the point power supply curve, and the conformal transformation method is only applicable to Line power can not be used for point power; although the line power and the point source electric field are different, it is still effective to use the electric cross-section curve of the line power supply to compare the electric profile curve of the point source with the comparison method.